Rethinking Antipsychotic Formulary Policy - Rosenheck, R.A. (Oxford University Press, 2008)
In this commentary, we review recent research suggesting that (a) second-generation antipsychotics (SGAs) may be no more effective than first-generation antipsychotics (FGAs), (b) the reduced risk of EPS and tardive dyskinesia with SGAs is more weakly supported by the research literature than has been appreciated, and (c) benefits may be offset by greater metabolic risks of some SGAs and their substantially greater cost. Bearing in mind, as well, that risperidone, currently the least expensive SGA, will soon be available as an even less expensive generic drug, we propose a new algorithm for maintenance antipsychotic therapy. We further outline a cautious implementation procedure that relies on standardized documentation and feedback, without a restrictive formulary that would limit physician choice. The algorithm outlined here and the process for its implementation are intended as a stimulus for discussion of potential policy responses, not as a finalized proposition.